2015
DOI: 10.1186/s12888-015-0693-5
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorder in Nyanza province, Kenya in 2013 and its associated risk factors –an assessment of change since 2004, using a repeat household survey in a demographic surveillance site

Abstract: BackgroundRepeat household surveys are useful to assess change in prevalence over time, but there have been no repeat surveys of common mental disorder (CMD) in Kenya, or indeed sub-Saharan Africa. Therefore a repeat household survey of CMD and its associated risk factors was conducted in Maseno area, Kisumu county in Kenya, using a demographic surveillance site as the sample frame, in order to test the hypotheses that (a) the prevalence of CMD would increase between 2004 and 2013 due to the intervening politi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 69 publications
3
28
1
Order By: Relevance
“…household surveys of common mental disorders were completed in the same area in 2004 and 2013 (Jenkins et al, 2015). The studies found a stable albeit much lower rate of mental disorders than in the current study of 10.8% in 2004 and 10.3% in 2013.…”
supporting
confidence: 39%
“…household surveys of common mental disorders were completed in the same area in 2004 and 2013 (Jenkins et al, 2015). The studies found a stable albeit much lower rate of mental disorders than in the current study of 10.8% in 2004 and 10.3% in 2013.…”
supporting
confidence: 39%
“…38,39 Given the sample size, it was possible during the calculation of the association measurement to adjust for confounder covariables, such as age, sex, family income, current smoking habits, alcoholic beverage consumption, and cardiovascular disease, in an attempt to neutralize their effect on the association under investigation. It is known that the prevalence of CMD varies according to age and sex, 5,40 as does periodontitis that increases in frequency and severity with age and is more prevalent among men. 41 Regarding socioeconomic condition, represented by family income, the frequency of CMD and periodontitis vary according to the distribution of income of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Although quite frequent, it is difficult to characterize . In international studies, the prevalence of CMD ranged from 10.30% to 43.70% . Population surveys conducted in 59 countries revealed that one in five people had CMD within a period of 12 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health experts estimate that a fourth of the Kenyan population of 44 million suffers from a range of the mental diseases, including the schizophrenia and the other psychotic disorders, bipolar disorder, depression and the severe anxiety [23]. However, Kenya has only about 80 psychiatrists and 30 clinical psychologists, fewer than its 500 psychiatric nurses, of which only 250 work in the mental health (Husain et al, 2016a).…”
Section: Mental Disorders In the African Contextmentioning
confidence: 99%